Legal Protection for Children as Victims of Narcotics Abuse (Research Study at the Belawan District Attorney's Office) - Endang Pakpahan; Alpi Sahari; Ahmad Fauzi (International Journal Reglement & Society (IJRS), 2022)
Children as drug abusers, are just victims. So it is not appropriate for the state to give punishment by looking at the same between child abusers and real adult criminals (dealers). As victims, children as narcotics abusers must get protection. Based on the results of an interview with Bastian Sihombing as the Head of the Pre-Prosecution at the Belawan State Prosecutor's Office, from 2019 to 2022 around 41 cases were resolved by diversion. This study aims to analyze the criteria for the age of children facing the law in narcotics crime, the factors that cause children to become victims of narcotics abuse and legal protection for children as victims of narcotics abuse at the Belawan District Attorney's Office. This research method uses empirical research with primary data types, by conducting interviews at the Belawan District Attorney. Based on the results of the study, the Belawan District Attorney's Office carried out rehabilitation measures as an effort to protect children from narcotics abuse victims in the juvenile criminal justice system, which must be pursued, with agreed terms and conditions set forth in conclusions and diversion agreements, or if rehabilitation must be carried out. the child will be immediately asked for an assessment by the integrated assessment team